Chlorophyll-a Distribution and Its Relation with Current Pattern in Northern Waters of Central Java - Bella Shabrina; Lilik Maslukah; Sri Yulina (Journal Omni-Akuatika, 2018)
Water fertility will determine the ammount of aquatic biotas (especially fish) that can live in the area. The high concentration of chlorophyll-a will show that water productivity in the area is high and fertile. The availability of chlorophyll-a in the waters is affected by oceanographic condition. One of them is the current pattern. The purpose of this study is to determine the distribution of chlorophyll-a spatially and temporally and its relation with current patterns in the northern waters of Central Java. The data that used in this research includes: chlorophyll-a data that obtained from level III Aqua MODIS imagery, current model data was obtained from MyOcean.eu, rainfall data, and sea surface temperature data that also obtained from Aqua MODIS satellite imagery. Sampling was done by purpossive sampling method. Distribution of chlorophyll-a that happened in Norrthern Waters of Central Java fluctuates every month. The largest concentration of chlorophyll-a was located close to the coastal area. The largest concentration of chlorophyll-a happened in June 2015 and 2016. Current pattern that happened in 2015 – 2016 changed every month and it was affecting the distribution of chlorophyll-a. However, the distribution of chlorophyll-a was not fully affected by the current pattern. There were several other factors such as river runoff and intensity of sunlight that could affect the chlorophyll-a distribution. Keywords : Chlorophyll-a, Phytoplankton, Current, Wind, Moonsoon